TLR4-dependant pro-inflammatory effects of HMGB1 on human adipocyte. (1st October 2016) - Gunasekaran, Manoj Kumar; Virama-Latchoumy, Anne-Laurence; Girard, Anne-Claire; Planesse, Cynthia; Guérin-Dubourg, Alexis; Ottosson, Lars; Andersson, Ulf; Césari, Maya; Roche, Régis; Hoareau, Laurence
ABSTRACT: Chronic low grade inflammation is one of the major metabolic disorders in case of obesity and associated pathologies. By its important secretion function, the role of adipose tissue in this metabolic low grade inflammation is well known. Recently, it was demonstrated that the alarmin high mobility group box protein 1 (HMGB1) is involved in obesity-related pathologies by its increased serum levels in obese compared to normal weight individuals, and by its pro-inflammatory effects. However, the role of HMGB1 on adipocytes inflammation is poorly documented and we propose to investigate this point. Primary culture of human subcutaneous adipocytes were performed from human adipose tissue samples. Cells were treated with recombinant HMGB1 with/without anti-TLR4 antibody and inhibitors of NF-κB and P38 MAPK. Supernatants were collected for IL-6 and MCP-1 ELISA. HMGB1 initiates Toll-like receptor 4 (TLR4)-dependent activation of inflammation through the downstream NF-κB and P38 MAPK signaling pathway to upregulate the secretion of the pro-inflammatory cytokine IL-6. HMGB1 has pro-inflammatory effects on adipocytes. This reinforces the role of TLR4 in adipose tissue inflammation and antagonizing the HMGB1 inflammatory pathway could bring on new therapeutic targets to counteract obesity-associated pathologies.